Fibroblast Growth Factor 23 and Left Ventricular Hypertrophy in Chronic Kidney Disease - Gutiérrez, Orlando M.; Januzzi, James L.; Isakova, Tamara; Laliberte, Karen; Smith, Kelsey; Collerone, Gina; Sarwar, Ammar; Hoffmann, Udo; Coglianese, Erin; Christenson, Robert; Wang, Thomas J.; deFilippi, Christopher; et al. (Circulation (New York, N.Y.), 2009)
Background— Fibroblast growth factor 23 (FGF-23) is a phosphorus-regulating hormone. In chronic kidney disease (CKD), circulating FGF-23 levels are markedly elevated and independently associated with mortality. Left ventricular hypertrophy and coronary artery calcification are potent risk factors for mortality in CKD, and FGFs have been implicated in the pathogenesis of both myocardial hypertrophy and atherosclerosis. We conducted a cross-sectional study to test the hypothesis that elevated FGF-23 concentrations are associated with left ventricular hypertrophy and coronary artery calcification in patients with CKD. Methods and Results— In this study, 162 subjects with CKD underwent echocardiograms and computed tomography scans to assess left ventricular mass index and coronary artery calcification; echocardiograms also were obtained in 58 subjects without CKD. In multivariable-adjusted regression analyses in the overall sample, increased log FGF-23 concentrations were independently associated with increased left ventricular mass index (5% increase per 1-SD increase in log FGF-23; P =0.01) and risk of left ventricular hypertrophy (odds ratio per 1-SD increase in log FGF-23, 2.1; 95% confidence interval, 1.03 to 4.2). These associations strengthened in analyses restricted to the CKD subjects (11% increase in left ventricular mass index per 1-SD increase in log FGF-23; P =0.01; odds ratio of left ventricular hypertrophy per 1-SD increase in log FGF-23, 2.3; 95% confidence interval, 1.2 to 4.2). Although the highest tertile of FGF-23 was associated with a 2.4-fold increased risk of coronary artery calcification ≥100 versus <100 U compared with the lowest tertile (95% confidence interval, 1.1 to 5.5), the association was no longer significant after multivariable adjustment. Conclusions— FGF-23 is independently associated with left ventricular mass index and left ventricular hypertrophy in patients with CKD. Whether increased FGF-23 is a marker or a potential mechanism of myocardial hypertrophy in CKD requires further study.